Antimicrobial Protein Produced By Lactobacillus Plantarum Atcc8014 In The Presence Of Cymbopogon Sp. Essential Oils - Hanina Mohd Noor; Salina Mat Radzi; Maryam Mohamed Rehan; Hairul Shahril Muhamad; Ismatul Nurul Asyikin Ismail; A’firah Mohd Sakri Shukri; Abdul Jalil Abdul Kader (Trans Tech Publications, Switzerland, 2024)
Applied Mechanics and Materials (Volumes 754-755)